THE POTENTIAL OF FOG AND DEW AS ALTERNATIVE CLEAN WATER SOURCES IN MOUNTAINEERING ACTIVITIES - Sri Rachmawati Hidayah Siregar (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2025)
Water exists in various phase, one of which is gases in air. Water harvesting from the air can be achieved using fog harvesting and dew harvesting technologies. In this research, the methods in each technology were qualitatively studied and supported by primary and secondary data for related parameters, namely temperature and relative humidity. Primary data were collected from Mount Merbabu and Mount Prau, while secondary data were obtained through internet searches. The test data concludes that all water harvesting methods have the potential to be applied in mountainous areas. Both traditional and modern methods are suitable for large-scale and permanent applications. Water harvesting using radiative cooling condenser passive system methods and solar regenerated desiccants in water harvesting passive system are suitable for savannah locations with sparse vegetation. Water harvesting from air using active cooling condensation methods are suitable for individual applications and can be made portable. Each method presents challenges that must be overcome to achieve optimal results.